2013
DOI: 10.1673/031.013.12101
|View full text |Cite
|
Sign up to set email alerts
|

New Artificial Diet for Continuous Rearing of the Bean Pod Borer,Maruca vitrata

Abstract: The bean pod borer, Maruca vitrata Fabricius (Lepidoptera: Crambidae), is a serious pantropical pest of grain legumes. A suitable artificial diet is desirable for producing uniform insects for commercial purposes or research. Three previously described artificial diets, 1 newly-developed artificial diet, and cowpea (Vigna unguiculata (L.) Walp. (Fabales: Fabaceae)), the natural hostplant of M. vitrata, were used for rearing M. vitrata, and the life parameters were examined. The results indicated that insects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
3
11
0
1
Order By: Relevance
“…These results implies that, the new artificial diet based on pigeonpea flour, leaf, flower, flower bud, tender pod powder and proportionate increased vitamins composition could be used as an alternative to natural hosts for rearing purposes. Our findings were in close agreement with Wang et al (2013) who reported many factors in the rearing process could affect the performance of M. vitrata on artificial diet, e.g., proportions of different nutritional ingredients, physical conditions of the diet (including moisture levels and irregularities of the diet surface), microbial contamination, several specific compounds, and environmental conditions in culture rooms.…”
Section: Results and Discussion I Comparison Of Developmental Paramesupporting
confidence: 92%
See 3 more Smart Citations
“…These results implies that, the new artificial diet based on pigeonpea flour, leaf, flower, flower bud, tender pod powder and proportionate increased vitamins composition could be used as an alternative to natural hosts for rearing purposes. Our findings were in close agreement with Wang et al (2013) who reported many factors in the rearing process could affect the performance of M. vitrata on artificial diet, e.g., proportions of different nutritional ingredients, physical conditions of the diet (including moisture levels and irregularities of the diet surface), microbial contamination, several specific compounds, and environmental conditions in culture rooms.…”
Section: Results and Discussion I Comparison Of Developmental Paramesupporting
confidence: 92%
“…This was followed by 30.6 ± 3.1, 26.6 ± 4.1, 21.8 ± 2.1 and 18.8 ± 1.1 in modified D-OOD, D-OOD, D-NEW and D-OO diet, respectively. These findings are in close agreement with Wang et al (2013) who reported rearing of M. vitrata for 8 successive generations without decline in the performance on new artificial diets and partially line with Onyango and Ochieng-Odero (1993) who reported that Maruca reared on soybean flour and cowpea flower powder as base ingredients in semi-synthetic diet for 10 successive generations.…”
Section: Results and Discussion I Comparison Of Developmental Paramesupporting
confidence: 91%
See 2 more Smart Citations
“…Maruca vitrata were collected as larvae from infested cowpea in the Cihui farm (Wuhan, China; 30°59'N 114°06'E) and reared on an artificial diet at 26 ± 1°C, and 60 ± 10 % relative humidity with a 14L:10D h photoperiod (lights off at 19:00 and on at 05:00) (Wang et al 2013). Sex-identified pupae were kept inside separate wooden cages (40 cm width × 50 cm length × 30 cm height) under the same environment conditions until moths emerged.…”
Section: Experimental Insectsmentioning
confidence: 99%